MED15 overexpression in prostate cancer arises during androgen deprivation therapy via PI3K/mTOR signaling - Offermann, Anne; Duensing, Stefan (OncoTarget, 2017)
Androgen deprivation therapy (ADT) is the main therapeutic option for advanced prostate cancer (PCa). After initial regression, most tumors develop into castration-resistant PCa (CRPC). Previously, we found the Mediator complex subunit MED15 to be overexpressed in CRPC and to correlate with clinical outcome. Therefore, we investigated whether MED15 is implicated in the signaling changes taking place during progression to CRPC. Immunohistochemistry (IHC) for MED15 on matched samples from the same patients before and after ADT reveals significantly increased MED15 expression after ADT in 72%.